Go West: The Westernization of Israeli Football in the Early Twenty-First Century. - Guy, Shlomit (Israel Studies Review)
This article discusses the transformations in Israeli football over the last two decades, exploring the top-down and bottom-up motivations present in local football and characterizing foreign practices as more Western, or even more 'civilized', as Norbert Elias would describe it. Yet, the transformations of English and European football over the last three decades suggest that 'Western' is not so much a geographic term as it is a political, moral, and social status, one requiring English, European, and Israeli football to make dedicated political and cultural investments in numerous arenas.